Environmental Life-Cycle Assessment of Waste Management in the Building Sector. A Case Study of a Building Project in Karlstad in Central-Sweden - Harge, Wilma; Venkatesh, G (Studia Ecologiae et Bioethicae, 2026)
The overarching objective of study is to carry out a detailed environmental life-cycle analysis (E-LCA), to quantify and understand the adverse (and beneficial) impacts, waste handling has on the environment, for a building project in Karlstad in central Sweden, which generated close to 574000 kilograms of diverse types of wastes. The study identifies the relevant environmental aspects of building-wastes management (a combination of recycling, incineration and landfilling, in other words), and avails of contribution, scenario and variation analyses to obtain and communicate some insights relevant and useful in a transition to a circular economy in the future. The emphasis on recycling plastics (which account for about 6% of the total mass), and not continuing to combust them in waste-to-energy plants is particularly strong. Quite obviously, recycling all metals and plastics, and resorting to forestry/garden wastes as a fuel source in lieu of plastics, shows tremendous climate change mitigation potential, in addition to contributing to a truncation of the acidification and eutrophication footprints of the life-cycles of buildings. Life-cycle thinking entails not just end-of-pipe waste management, but also re-designing and re-thinking on the upstream (for reusability, durability, recyclability), and trans-materialising and dematerializing from the point of view of minimising the amounts of waste generated. The study implicitly points at the need for not just continued research in the field of waste management in general (SDG 9), but also sustained collaboration among several stakeholders in the fray (SDG 17), which was gathered from the interviews carried out by the first author to incorporate the social dimension of the sustainability of waste management.